Frontiers of Philippine public administration, regulatory policymaking and contract management. IN Reflections from Scholars and Practitioners [column] LTFRB, PPP and BRT - Ocampo, Romeo B. (Philippine Journal of Public Administration, 2012)
Government administration has undergone such radical rolling-back reforms that it would appear to have been left with little to do but regulate private functions and contract out what remains of public ones. Privatization, deregulation, and other such programs have foundered, and vestiges of the old Public Administration (PA) have proved more resilient than exponents of roll-back-the-state reforms have hoped. Still, regulation and contract administration are no small tasks and have assumed greater importance of governance in view of the larger roles assigned to private business, the market, and civil society. Many regular departments make and apply rules that are not law but may have the effect of law on a wide variety of matters that directly or ultimately affect the public. Such rulemaking power of administrative agencies must be delegated by the legislature, and it must be exercised within statutory law and the constitution. The article's aim is, first, to examine the nature and importance of administration in the Philippines and the U.S.; second, to try to document more fully the impression of the neglect of meta-rules for rulemaking here; and third, to explore the possibilities and problems of developing such rules, including those suggested by American experience. The article also introduces contract administration as a form of regulation by specific terms and conditions, which specific parties agree to abide by.